2018
DOI: 10.1007/s00210-017-1450-8
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol, a β-blocker abrogates streptozotocin-induced behavioral, biochemical, and neurophysiological deficit by attenuating oxidative-nitrosative stress: a possible target for the prevention of diabetic neuropathy

Abstract: Metabolic abnormalities including hyperglycemia, hyperlipidemia, and oxidative-nitrosative stress are involved in the progression of diabetic neuropathy. In the present study, we targeted oxidative-nitrosative stress using nebivolol, a β-receptor antagonist with vasodilator and antioxidant property, to evaluate its neuroprotective effect in streptozotocin-induced diabetic neuropathy in rats. Diabetic neuropathy develops within 4-6 weeks after administration of streptozotocin (55 mg/kg, i.p.). Therefore, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Diabetes mellitus (DM) is a complex metabolic disorder which adversely affects multiple physiological systems including the central nervous system and cardiovascular system, and the disease is associated with altered memory function, cardiac stress, endothelial dysfunction and neuropathy (Islam et al, 2017; Bhadri et al, 2018; Minaz et al, 2018). Both type 1 and type 2 diabetes induce changes in the neurones, brain and memory as seen in the case of Alzheimer’s disease (Zhao and Townsend, 2009; Ouwens et al, 2014; Rdzak and Abdelghany, 2014; King et al, 2015; Meneilly and Tessier, 2016; Morales-Corraliza et al, 2016; Chen et al, 2018; Pappas et al, 2018; Takeuchi et al, 2018; Yashkin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a complex metabolic disorder which adversely affects multiple physiological systems including the central nervous system and cardiovascular system, and the disease is associated with altered memory function, cardiac stress, endothelial dysfunction and neuropathy (Islam et al, 2017; Bhadri et al, 2018; Minaz et al, 2018). Both type 1 and type 2 diabetes induce changes in the neurones, brain and memory as seen in the case of Alzheimer’s disease (Zhao and Townsend, 2009; Ouwens et al, 2014; Rdzak and Abdelghany, 2014; King et al, 2015; Meneilly and Tessier, 2016; Morales-Corraliza et al, 2016; Chen et al, 2018; Pappas et al, 2018; Takeuchi et al, 2018; Yashkin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation response to EFS in the diabetic group was enhanced in the presence of mirabegron which may be due to the neuroprotective effect of mirabegron through its NO-potentiating activity in the cavernosal nerve. Also, another study demonstrated that nebivolol was beneficial in the treatment of diabetic neuropathy [15]. A study by Oikawa et al [16] demonstrated protective effects of the β 3 -AR agonist CL316243 against N-methyl-D-aspartate-induced retinal neurotoxicity in rats by stimulation of β 3 -ARs.…”
Section: Discussionmentioning
confidence: 98%
“…Streptozotocin is widely used to induce diabetes because STZ-induced experimental diabetic rats exhibit well-characterized diabetic complications and sustained hyperglycemia with a low incidence of mortality [ 12 14 ]. Here, STZ-induced diabetes rats were constructed to investigate the potential role of AVP and RVP in the development of DN.…”
Section: Discussionmentioning
confidence: 99%